The Effect of Loss and Optimization Functions on Bitcoin Rate Prediction in LSTM - KIRCI, BERKE KAAN; BAYDOĞMUŞ, GÖZDE KARATAŞ (Institute of Electrical and Electronics Engineers Inc., 2022)
In recent years, Bitcoin cryptocurrency has become a growing trend in the world. For this reason, researchers from many fields are examining various artificial intelligence models to predict Bitcoin rates. In particular, Deep Learning algorithms have been shown to outperform traditional models in predicting cryptocurrency rates. However, very few studies have examined the effect of parameters used in deep learning algorithms on the algorithm. Optimization and loss functions are very important, which affect the algorithm's ability to make a successful prediction. In this study, Long-Short Term Memory, a deep learning algorithm, is used to predict daily Bitcoin prices and the effect of optimization/loss functions on the accuracy rate is evaluated. Experimental results showed that the Long-Short Term Memory model made the best predictions as a result of working with the Adam optimization function and the Mean Square Error loss function. © 2022 IEEE.
4th International Congress on Human-Computer Interaction, Optimization and Robotic Applications, HORA 2022
Keywords: Bitcoin; Loss Function; LSTM; Optimization Function